2005
DOI: 10.1016/j.bbr.2004.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Odor detection of single chemicals and binary mixtures

Abstract: The investigation explored the olfactory detectability of two chemically and structurally similar esters, ethyl propanoate and ethyl heptanoate, presented singly and in mixtures. Initially, we measured concentration-detection (i.e., psychometric) functions for the odor of ethyl propanoate and ethyl heptanoate presented singly. Using this information, we prepared binary mixtures of the two chemicals in varying complementary proportions and, also, selected concentrations of the single compounds, such that, if a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 55 publications
4
43
0
1
Order By: Relevance
“…On the contrary, at a detectability of 0. [51] At high detectability levels there is again a clear hypoaddition with respect to the response addition model, while at lower detectability levels, the experimental detectability of the mixture fits exactly the response-addition model Whisky lactone/isomyl acetate; whisky lactone/ethyl butyrate; guaiacol/ethyl butyrate 2005 [63] In all cases the presence of woody odorants caused a significant difference. The degree of the difference increases with the concentration.…”
Section: Eight Chemicals 1963mentioning
confidence: 81%
See 2 more Smart Citations
“…On the contrary, at a detectability of 0. [51] At high detectability levels there is again a clear hypoaddition with respect to the response addition model, while at lower detectability levels, the experimental detectability of the mixture fits exactly the response-addition model Whisky lactone/isomyl acetate; whisky lactone/ethyl butyrate; guaiacol/ethyl butyrate 2005 [63] In all cases the presence of woody odorants caused a significant difference. The degree of the difference increases with the concentration.…”
Section: Eight Chemicals 1963mentioning
confidence: 81%
“…As shown in the table, there are very early reports about mixtures of odour chemicals at threshold or sub-threshold levels. The most extensive [ 51,60,61] Intensity and detectability of odor mixtures [34] and part of it was even published in the journal Nature. [35] These authors demonstrated that the odour activity values (OAVs), or concentration/threshold ratios of mixtures of odorants at sub-threshold values are approximately additive.…”
Section: Mixtures Of Odorants At Threshold Levels the Odour Activity mentioning
confidence: 99%
See 1 more Smart Citation
“…There is a long tradition in studying behavioral responses to odor mixtures both in vertebrates (Laing and Francis, 1989;Kay et al, 2003Kay et al, , 2005Wiltrout et al, 2003;Cometto-Muniz et al, 2005) and invertebrates (Derby et al, 1996;Smith, 1998;Deisig et al, 2003), and technical advances have recently allowed a physiological approach. Studies in vertebrates analyzed the peripheral level (Duchamp-Viret et al, 2003;Oka et al, 2004), the olfactory bulb (Giraudet et al, 2002;Tabor et al, 2004;Lin et al, 2005) and the olfactory cortex (Lei et al, 2006;Zou and Buck, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of sensory irritation thresholds (NPTs and EITs) from mixtures of VOCs have shown various levels of additivity that, to a first approximation, are not-too-far from complete additivity (Nielsen et al, 1988;Cometto-Muñiz et al, 1997;1999;2001a;2004a;2004b). So are results from studies on ODTs 2005b;Wise et al, 2007;Miyazawa et al, 2009). To extend occupational exposure limits to mixtures of VOCs, additivity of effects has been suggested (Alarie et al, 1996).…”
Section: Introductionmentioning
confidence: 99%